Pengaruh penambahan tepung ikan teri hitam (Stolephorus insularis) terhadap karakteristik kimia dan tekstur pizza base: The addition of anchovy (Stolephorus insularis) powder to chemical and texture characteristics of pizza base - Dina Shofa Istifada; Fronthea Swastawati; Ima Wijayanti (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2023)
Anchovies have high protein and calcium content; hence, they can be fortified on a pizza base. The fortification of anchovy meal can be an alternative to increasing fish consumption through product diversification. This study aimed to determine the physical, chemical, and sensory characteristics and optimal concentration of pizza base with the addition of anchovy meal. The treatments used in this study included the addition of anchovy meal at concentrations of 0, 4, 6, and 8% on a pizza base with three replicates. The parameters tested were protein, fat, carbohydrate, ash, moisture, calcium content, cohesiveness, and hedonic value. This research used a completely randomized design model and statistical data processing using SPSS 25. Parametric data were analyzed using the variance test (ANOVA) and honest significant difference (BNJ), while non-parametric data were analyzed using the Kruskal-Wallis test. The results showed that pizza-based anchovy meal had a significant effect (p<0.05) on increasing protein, fat, ash, and calcium, as well as carbohydrate, moisture, cohesiveness, and hedonic values. Concentration of 8% had better nutritional value, but pizza base with 4% anchovy meal was the most preferred by panelists. The results of the pizza base hedonic test with the addition of anchovy flour concentration of 4% had an average value of 8.39±0.54 based on the parameters of color, taste, texture and aroma. Nutritional content of pizza base with the addition of 4% anchovies were protein 17.39±0.44%, lipid 5.15±0.03%, carbohydrate 75.73±0.41%, ash 1.73±0.02%, moisture 7.42±0.69%, calcium 239.87±0.76 mg/100 g and cohesiveness 0.71±0.02. The hedonic score showed that panelists preferred 4% anchovy meal added to the pizza base, with an average value of 8.39±0.54. Pizza base with the best nutrition dan hedonic is concentration of 4%. The addition of anchovy meal increased nutrition value of pizza base with sensorial acceptable